Det unaturlige i fortællende poesi. To radikale eksempler - McHale, Brian (K&K - Kultur og Klasse, 2011)
THE UNNATURALNESS OF NARRATIVE POETRY | New cognitive theory (e.g. Monica Fludernik) argues that we naturalize texts by narrativizing them. Although there are no ultimately “unnatural” narratives on this account, this article argues that there are certainly artificial ones. The article focuses especially on narrative poetry in which the artificial order of poetry spaces language and denaturalizes it. It is the underlying hypothesis that artifice changes everything, narrative included. And the article shows this in a contrastive reading of two very different narrative poems: Shakespeare’s Venus and Adonis that exploits the possibility of artificial segmentation, heightened diction and extravagant figuration and Les Murray’s Fredy Neptune: A Novel in Verse in which narration dominates, artifice is minimal, reduced to little more that lineation, stanza-breaks and sporadic end-rhymes. The point is that even in the case of Les Murray’s very narrative poetry, the artificial segmentation sets up counter-rhythms that syncopate and counterpoint narrative shifts.